Adoption of E-Business Technologies and Suppliers Performance in Thai Automotive Supply Chains - Farooquie, Parveen; Farooquie, Jamal A. (UI Scholars Hub, 2009)
Collaborative efforts, economies of time and cost, competitive service quality, and technological flexibility are among the key concerns of operations for successful supply chains. Implementation of web-based technologies has contributred significantly towards the achievement of such objectives of supply chains. The presents study examines the various aspects of e-business technologies adoption with reference to the first-tier suppliers associated with the automotive supply chains in Thailand. The paper also investigates the impact of employing e-business technologies on the suppliers' performance.